Deskripsi tipe pertanyaan siswa berdasarkan sifatnya pada kegiatan menanya dalam pembelajaran matematika dengan pendekatan saintifik - Sudarmanti, Sudarmanti; Supriyono, Supriyono; Sapti, Mujiyem; Rochim, Abdul (Universitas Muhammadiyah Purworejo, 2020)
The purpose of this research to describe the type of student question on learning mathematics with a scientific approach. This research at the tenth-grade student of SMA Negeri 7 Purworejo in the academic year of 2019/2020. The design of the study used descriptive quantitative. This research using purposive sampling. The research took 36 students of X MIA 6. The researchers analyzed the data by using observation, video record, and field notes. The study results show that the type of question many students convey is remembering information, concept understanding, and concept applying in learning material.